1983
DOI: 10.1080/01904168309363092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aluminum on organic acid, sugar and amino acid composition of the root system of sorghum (Sorghum bicolorL. Moench)

Abstract: The effects of aluminum on the accumulation of sugars, amino acids and organic acids in two hybrid cultivars of sorghum were studied.The concentration of these organic compounds increased in the roots of the Al-treated plants, mainly in the tolerant cultivar. The composition of the organic acid fraction showed a significantly higher accumulation of trans-aconitate and malate in the tolerant cultivar as compared with the sensitive one. The higher levels of these acids in the Al-treated plants could be interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
4

Year Published

1985
1985
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 13 publications
3
23
0
4
Order By: Relevance
“…Lee & Foy (1986) também encontraram, em extratos de raízes de feijão, maiores acúmulos de ácidos na cultivar tolerante, com 52%, contra 48% na cultivar sensível. Cambraia et al (1983) também encontraram maiores acúmulos de ácidos na cultivar tolerante de sorgo, com 69%, contra 31%, na cultivar sensível. Na solução com Al, houve um decréscimo na produção de ácidos orgâni-cos em relação à solução sem Al; este decréscimo foi maior no grupo das cultivares sensíveis (interação cultivar vs Al).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Lee & Foy (1986) também encontraram, em extratos de raízes de feijão, maiores acúmulos de ácidos na cultivar tolerante, com 52%, contra 48% na cultivar sensível. Cambraia et al (1983) também encontraram maiores acúmulos de ácidos na cultivar tolerante de sorgo, com 69%, contra 31%, na cultivar sensível. Na solução com Al, houve um decréscimo na produção de ácidos orgâni-cos em relação à solução sem Al; este decréscimo foi maior no grupo das cultivares sensíveis (interação cultivar vs Al).…”
Section: Resultsunclassified
“…A maceração de cada amostra foi feita em um gral e pistilo de porcelana, em 10 mL de etanol a 80% e mais 10 mL para a limpeza, durante 15 minutos, à temperatura ambiente do laboratório. As amostras trituradas foram guardadas em tubos de ensaio na geladeira, a 5°C, por 24 horas (Cambraia et al, 1983). O extrato foi removido do material macerado, por centrifugação a 20.000 g, durante 15 minutos, em duas extrações consecutivas.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…The following organic acids were able to protect calmodulin from the deleterious effects of Al in the order: citric > oxalic > malic > tartaric (26,27). These results demonstrate that organic acids could protect enzyme activity internally in the plant from the deleterious effect of Al. Evidence of internal detoxification by organic acids was presented by Cambraia et al (5), who showed that the overall response of sorghum (Sorghum bicolor Moench) roots to Al was an increase in organic acid content. Moreover, the roots of the Al-tolerant sorghum cultivar contained higher levels of organic acids, particularly t-aconitic and malic acids, than did the Al-sensitive cultivar (5).…”
mentioning
confidence: 98%
“…These results demonstrate that organic acids could protect enzyme activity internally in the plant from the deleterious effect of Al. Evidence of internal detoxification by organic acids was presented by Cambraia et al (5), who showed that the overall response of sorghum (Sorghum bicolor Moench) roots to Al was an increase in organic acid content. Moreover, the roots of the Al-tolerant sorghum cultivar contained higher levels of organic acids, particularly t-aconitic and malic acids, than did the Al-sensitive cultivar (5). However, in the roots of snapbeans, the overall response to Al was a reduction in organic acid contents, although the Al-tolerant snapbean cultivar maintained a higher level of organic acids than did the Alsensitive cultivar (20).…”
mentioning
confidence: 98%